Prevalencia del síndrome metabólico en la población masculina del personal docente y administrativo del área biológica de la Universidad Técnica Particular de Loja sede Loja, año 2017 - Merino Peralta, Carlos Xavier (2018)
Abstract:The objective of the present research was to establish the prevalence of metabolic syndrome in the male population of teaching and administrative staff of the Universidad Técnica Particular de Loja, Loja, period 2017. In the present descriptive cross sectional study, the components of the metabolic syndrome were measured clinically and analytically, applying the diagnostic criteria established by the Adult Treatment Panel III. The sample consisted of 52 males, the most frequent age ranges being 30 to 39 years and 40 to 49 years, followed by the range of 50 to 59 years. A total number of 5.76% of people with metabolic syndrome was present, with a greater number in the age group from 40 to 49 years old, with elevated blood pressure being the criterion most frequently found, in addition to individually analyzing the criteria, Triglycerides was predominant with 48.07% with an average of 170.11 mg / dl, followed by HDL cholesterol <40 mg / dL.